2019
DOI: 10.2147/cia.s212334
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lung ultrasound score-based perioperative assessment of pressure-controlled ventilation-volume guaranteed or volume-controlled ventilation in geriatrics: a prospective randomized controlled trial</p>

Abstract: Purpose Recent studies have shown the potential benefits of pressure-controlled ventilation-volume guaranteed (PCV-VG) compared to volume-controlled ventilation (VCV), but the results were not impressive. We assessed the effects of PCV-VG versus VCV in elderly patients by using lung ultrasound score (LUS). Patients and methods Elderly patients (aged 65–90 years) scheduled for hip joint surgery were randomly assigned to either the PCV-VG or VCV group during general anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Of those, 351 had to be excluded, resulting in 21 publications that were full-text assessed for eligibility. Four publications had to be excluded, finally resulting in 17 studies that underwent the following qualitative evaluation [ 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A flow chart of the search strategy and study selection are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 351 had to be excluded, resulting in 21 publications that were full-text assessed for eligibility. Four publications had to be excluded, finally resulting in 17 studies that underwent the following qualitative evaluation [ 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A flow chart of the search strategy and study selection are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 24 In previous research on LUS scores based on ventilation mode in elderly patients, a PCV-VG group had lower LUS scores compared to a VCV group, which suggests that the distribution of ventilation and LUS score may vary depending on the ventilation mode. 25 …”
Section: Discussionmentioning
confidence: 99%
“…PCV-VG is a mechanical ventilation mode that guarantees TV with the lowest possible pressure using decelerating flow for patients undergoing surgery. [ 13 14 15 ] As for our 2 cases, intraoperative high airway pressures and barotrauma were also of great concern, therefore, PCV-VG ventilation mode was adjusted for each patient. It was also reported that spontaneous ventilation should be maintained for as long as possible and that the inspiratory pressure should be kept under 20 cmH 2 0 even if muscle relaxants were used.…”
Section: Discussionmentioning
confidence: 99%